DEVELOPMENT OF INTERSPECIFIC HYBRID ROOTSTOCKS USING CUCURBITAMOSCHATA DUCH EX. POIRAND CUCURBITA MAXIMA LINES - N.A.Tamilselvi; T.Arumugam (Journal of Animal and Plant Sciences, 2022)
In recent years, vegetable grafting has emerged as a rapid tool in tailoring plants to adapt to climate resilient growing conditions. Utilization of grafting technique is increasing mainly in commercial cucurbitaceous vegetables viz., watermelon, cucumber, bitter gourd and muskmelon. These vegetables are preferably grafted withinterspecific hybrid rootstocks fortheir seedling vigor, high degree of resistance againstbiotic and abiotic stresses. Moreover, the hybrid rootstock increases the yield of respective scions. To harness the potentiality of rootstocks, an attempt has been made to develop interspecific hybrid rootstocks by using 48 Cucurbita moschata and four Cucurbita maximalinesand hybridization was attempted through Line x Tester mating design. These 52 genotypes were collected from various diverse agro climatic regions ofIndia and World Vegetable Centre, Taiwan, raised by following proper isolation distance and selfed to maintain the genetic purity. Using 48 Cucurbita moschata genotypes as lines and four Cucurbita maximagenotypes astesters, 192 interspecific hybrids were developed, out of which only 16 hybrids were fertile and in rest of the hybrids, cross incompatibility was observed. Among the lines, CMo 28, CMo 43 and CMo 44 were highly cross compatible with different Cucurbita maxima testers. Among the testers, CMa 49 and CMa 52 were highly cross compatible with different Cucurbita moschata lines. Among the fertile hybrid rootstocks, CMo 44 × CMa 52, CMo 28 × CMa 52 and CMo 43 × CMa 51 were identified as promising ones and used for graftingstudies.
Keywords: Interspecific hybrid rootstocks; pumpkin; Cucurbita moschata; winter squash and Cucurbita maxima